1994
DOI: 10.1023/a:1018911926190
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Skin permeability of drugs was evaluated based on the hydrodynamic pore theory. Four polar solutes were used, with differing molecular sizes--ethylene glycol, 1,3-butylene glycol, antipyrine and sucrose--and isosorbide dinitrate was also selected as a lipophilic drug. The skin permeations of solvent (D2O) and one of these drugs were measured simultaneously under various osmotic pressures to calculate the reflection coefficient. The clearance of isosorbide dinitrate was independent of the solvent flux, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…11,16,21,24,25 It should be kept in mind that there are obvious limitations in applying any manageable model to describe transport through a complex, heterogeneous membrane such as HEM. 11,16,21,24,25 It should be kept in mind that there are obvious limitations in applying any manageable model to describe transport through a complex, heterogeneous membrane such as HEM.…”
Section: Resultsmentioning
confidence: 99%
“…11,16,21,24,25 It should be kept in mind that there are obvious limitations in applying any manageable model to describe transport through a complex, heterogeneous membrane such as HEM. 11,16,21,24,25 It should be kept in mind that there are obvious limitations in applying any manageable model to describe transport through a complex, heterogeneous membrane such as HEM.…”
Section: Resultsmentioning
confidence: 99%
“…( n =3–4 independent samples). The osmotic concentration differential was adjusted to 3.08, 0, –3.08 mol/L by adding NaCl to donor or receiver compartments 15 .…”
Section: Methodsmentioning
confidence: 99%
“…It also showed that the enhancement of the skin permeability of a drug by EtOH at a low concentration was due to the action on skin lipids (34,35) and solvent drag effect (36)(37)(38). The former could be characterized as a rather "static effect" mainly governed by the integral amount of EtOH acting on the skin lipids.…”
Section: Resultsmentioning
confidence: 99%